PENGARUH LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KINERJA PETUGAS PADA UNIT AVSEC (AVIATION SECURITY) PADA MASA PANDEMI COVID-19 DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Alya Maharani Putri; Kifni Yudioanto, S.E., M.M (Pusat Riset dan Inovasi Nasional, 2023)
The Covid-19 pandemic is very dangerous and has resulted in many activities being delayed and causing new regulations to prevent it. The Covid-19 pandemic has also had an impact on air transportation modes, especially for Avsec (Aviation Security) officers. The purpose of this study was to determine whether the work environment and discipline had an effect on the performance of Avsec officers at Juanda International Airport, Surabaya. Using the quantitative method a sample of 80 Avsec officers. Data was collected by distributing questionnaires, which were then processed through SPSS version 25. As a result of the study, there was a significant simultaneously and partially significant effect on the performance of Avsec officers with a significance value of 0.00 < 0.05 and a significant value of work environment variable 0, 00 < 0.05 means that the work environment partially affects the performance of Avsec officers, while the discipline variable has a significant value of 0.00 < 0.05, which means that the discipline variable affects the performance of Avsec officers. The effect of work environment and discipline on Avsec (Aviation Security) officers is 69.1% while the remaining 30.9% is influenced by other variables.